Generalist Early Education and Specialist Physical Education Teachers’ Views on the Scope of Early Childhood Physical Education - DIAMANTI, Ioanna; Dania, Aspasia; Venetsanou, Fotini; Irene Kamberidou (Pamukkale Journal of Sport Sciences, 2023)
Citation: Diamanti, I., Dania, A., Venetsanou F., and Kamberidou, I. (2023). Generalist Early Education and Specialist Physical Education Teachers’ Views on the Scope of Early Childhood Physical Education. Pamukkale Journal of Sport Sciences, 14(2), 167-191. https://doi.org/10.54141/psbd.1234072  © 2023 The Author(s) available online at https://dergipark.org.tr/en/pub/psbd .